2016
DOI: 10.1186/s12889-016-2985-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of Australian early childhood education and care experiences: study protocol

Abstract: BackgroundIn Australia, 61.5 % of children aged 3–4 attend Early Childhood Education and Care (ECEC) programs. Children’s experiences within these programs vary widely and impact directly on educational wellbeing and social development. Research has shown that higher quality programs enhance children’s learning and developmental outcomes, foster social participation and have long-lasting effects on their productivity as adults. Quality matters, yet we do not know what components of ECEC result in a quality pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 4 publications
2
46
0
4
Order By: Relevance
“…For example, validation studies (Downer et al 2010;Pakarinen et al 2010) or studies that have compared CLASS Pre-K with others instruments that assess quality (LaParo et al 2004) or studies that assess the stability of interactions during the day (Curby et al 2010). A few studies have focused on relationships between CLASS Pre-K and outcomes such as educational wellbeing and social development (Burchinal et al 2008;Curby et al 2009;Tayler et al 2016) or assessed the relationship between CLASS Pre-K scores and service type (Tayler et al 2013). These studies consistently found that higher quality interactions resulted in improved outcomes for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, validation studies (Downer et al 2010;Pakarinen et al 2010) or studies that have compared CLASS Pre-K with others instruments that assess quality (LaParo et al 2004) or studies that assess the stability of interactions during the day (Curby et al 2010). A few studies have focused on relationships between CLASS Pre-K and outcomes such as educational wellbeing and social development (Burchinal et al 2008;Curby et al 2009;Tayler et al 2016) or assessed the relationship between CLASS Pre-K scores and service type (Tayler et al 2013). These studies consistently found that higher quality interactions resulted in improved outcomes for children.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment is based on three core domains of interactions: emotional support, classroom organization and instructional support. Although predominantly used for assessment in US classrooms, CLASS Pre-K has been validated across a range of classrooms, for example, in ECEC centers with diverse languages (Downer et al 2010), in various countries (Pakarinen et al 2010;Tayler et al 2016) and in comparison to other assessments of quality such as ECERS (LaParo et al 2004). Findings indicate that CLASS Pre-K operates consistently across centers, demonstrating that it could function as a tool for improving quality in ECEC centers (Pianta et al 2008).…”
Section: Assessment Of Quality In Early Childhood Education and Care mentioning
confidence: 99%
“…identifying and determining the quality of educational programs for early childhood can be seen from assessments made by teachers to students in the learning process through play activities. That is, that student assessment is one of the benchmarks of the quality of early childhood programs [5]. Authentic assessment is required to demonstrate student ability, provide feedback and direction for its growth and development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Your unwavering support, encouragement and belief in my ability certainly gave me the will to keep going during those challenging times. Carnegie Task Force on Meeting the Needs of Young Children, 1994;McCain & Mustard, 1999;OECD, 2001OECD, , 2006OECD, , 2011OECD, , 2015Shonkoff & Phillips, 2000;Tayler et al, 2016). Findings of studies in developmental science reveal that the effects of children's participation in preschool programs to be positive for children in both short-term and long term outcomes (Burchinal et al, 2008;Karoly, Kilburn, & Cannon, 2006;Landry et al, 2014;Mashburn et al, 2008;Sammons et al, 2002;Sylva, Melhuish, Sammons, Siraj-Blatchford, & Taggart, 2004b).…”
Section: My Amazing Village!mentioning
confidence: 99%
“…Research focussing on ECEC provides powerful evidence that interaction, including teacher-child interaction, is a key to quality (National Institute of Child Health and Human Development, 2006;Siraj-Blatchford et al, 2002;SirajBlatchford & Sylva, 2004;Sylva et al, 2004b;Tayler et al, 2016). The European longitudinal study, The Effective Provision for Pre-School Education (EPPE) (1997)(1998)(1999)(2000)(2001)(2002)(2003)) (Siraj-Blatchford & Sylva, 2004;Sylva et al, 2004a) tracked the progress of 3000 children aged between 3 and 7 years in 141 preschools in England.…”
Section: Social Interaction: Identified As a Key To Qualitymentioning
confidence: 99%